IMPLEMENTASI PROGRAM MAHASISWA WIRAUSAHA DI UNIVERSITAS GADJAH MADA - , MUGI RAHAYU WILUJENG; , Dr. Erwan Agus Purwanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The great unemployment number of people with high educational level in Indonesia has become a major serious problem. Due to this matter, DIKTI, as a governmental institution which has concerns on educational matters, initiates Entrepreneurship Students Program / Program Mahasiswa Wirausaha (PMW) in order to create new entrepreneurs who are equipped with good educational background and have good visions, particularly providing job opportunities. The Program has been implemented since 2009 in several public and private universities in Indonesia, including Universitas Gadjah Mada (UGM). CED (Center for Entrepreneurship Development), under the coordination of UGM Students Directorate, has a role as the main implementer which is in charge to monitor the implementation of PMW UGM. This research aims to find out the achievement of PMW UGM implementation in improving the skills of student entrepreneurs to be tough and successful entrepreneurs in facing the global challenge and competition